2007
DOI: 10.1016/j.powtec.2007.02.027
|View full text |Cite
|
Sign up to set email alerts
|

From compressibility to structural investigation of sodium dodecyl sulphate — Part 1: Powder and tablet physico-chemical characteristics

Abstract: 7 pagesInternational audienceAs a part of a study on detergent tablets, investigations were carried out to elucidate the compression behavior of a powdered surfactant, sodium dodecyl sulphate (SDS), based on a comparison with the main component of the formulation, i.e. the chorine provider (DCCNa). The compacted SDS exhibited poor cohesion as well as delayed dissolution whatever the compression pressure. The microscopic observations and the mercury porosimetry measurements both demonstrated that a residual por… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The agglomerates (compressed tablets, 13 mm diameter and 4.5 mm height) were prepared by using a Carver hydraulic laboratory press (Model C S/N 32 000‐224, Carver Inc., Wabash, IN, USA) working with a 75 MPa die (WQ09D; Perkin Elmer, Cambridge, UK) and pouring 0.7 g of the powder samples (corresponding to each of the eight sieved fractions) into the die for powder compression 18, 19. Two compaction forces, 75 MPa (A agglomerates) and 225 MPa (B agglomerates), were applied to form the agglomerates.…”
Section: Methodsmentioning
confidence: 99%
“…The agglomerates (compressed tablets, 13 mm diameter and 4.5 mm height) were prepared by using a Carver hydraulic laboratory press (Model C S/N 32 000‐224, Carver Inc., Wabash, IN, USA) working with a 75 MPa die (WQ09D; Perkin Elmer, Cambridge, UK) and pouring 0.7 g of the powder samples (corresponding to each of the eight sieved fractions) into the die for powder compression 18, 19. Two compaction forces, 75 MPa (A agglomerates) and 225 MPa (B agglomerates), were applied to form the agglomerates.…”
Section: Methodsmentioning
confidence: 99%
“…For a detailed discussion of the characteristics of the parameters listed in Table 1, the authors recommend Refs. [18,19] for further reading.…”
Section: Tablet Composition and Characteristicsmentioning
confidence: 99%
“…However, for most crystallization processes, surfactants are used as an additive to modify crystal properties, to assemble mesocrystals (three-dimensionally well-aligned nanosized particles), or to affect nucleation and crystal growth through the manipulation of interfacial tension . Only a few studies on surfactant crystallization itself were reported, and yet, a diversity of crystal attributes, such as polymorphs and pseudo-polymorphs, morphologies, and size distributions of a crystalline substance, have implications in downstream processing characteristics and product performance. For instance, flowability, compressibility (i.e., tabletability), and dissolution rate are often considered for powdered detergents or tablets . The understanding of surfactant crystallization can definitely help in the control of those attributes of a product surfactant for surfactant-based products, especially when the crystallization mechanisms for surfactant systems are complex.…”
Section: Introductionmentioning
confidence: 99%
“…15−17 For instance, flowability, compressibility (i.e., tabletability), and dissolution rate are often considered for powdered detergents or tablets. 18 The understanding of surfactant crystallization can definitely help in the control of those attributes of a product surfactant for surfactant-based products, especially when the crystallization mechanisms for surfactant systems are complex. When the surfactant concentration is above the critical micelle concentration (CMC), its kinetic processes of micelle formation and crystal nucleation are competing with each other.…”
Section: ■ Introductionmentioning
confidence: 99%